Improved Tumor Control Related to Radiotherapy Technological Development for Hypopharyngeal Cancer. (12th May 2020) - Susko, Matthew S.; Lazar, Ann A.; Dhar, Shwena; Chan, Jason W.; Shiao, Stephen L.; Chapman, Christopher H.; Johnson, Julian; Quivey, Jeanne M.; Ryan, William R.; Heaton, Chase M.; Ha, Patrick K.; Yom, Sue S.
Abstract : Objectives/Hypothesis: Squamous cell carcinoma of the hypopharynx (SCCHP) is associated with worse survival compared to other head and neck subsites. This report quantifies the impact of technological improvements in radiotherapy (RT) on outcomes over 6 decades. Methods: Patients with SCCHP receiving curative‐intent treatment between 1962 and 2015 were retrospectively reviewed. Kaplan‐Meier analyses of freedom from local recurrence (FFLR), progression‐free survival (PFS), and overall survival (OS) were compared across treatment eras and radiation techniques. Multivariable Cox proportional hazards modeling was performed to specify the effect of RT technique. Results: One hundred thirty‐four patients had a median follow‐up of 17 months (IQR = 9–38). There were no differences in staging or use of surgery over time, but use of chemotherapy concurrent with RT increased ( P  < .001) beginning in the 2000s. The 24‐month FFLR using two‐dimensional RT (2D‐RT), three‐dimensional conformal RT (3D‐CRT), and intensity‐modulated RT (IMRT) was 52%, 55%, and 80%, respectively; 24‐month PFS was 39%, 46%, and 73%, respectively; and 24‐month OS was 27%, 40%, and 68%, respectively. OS ( P = .01), PFS ( P = .03), and FFLR ( P = 0.02) were improved with IMRT over 2D‐RT, and FFLR appeared to be improved over 3D‐CRT ( P = .06). Controlling for chemotherapy use and other major variables, IMRT produced a strong influence over FFLR (adjusted hazard ratio [HR] = 0.2, 95% confidence interval [CI]: 0.0‐1.2, P = .08) and a benefit in OS (adjusted HR = 0.1, 95% CI: 0.0‐0.4, P = .005). Conclusions: Across 6 decades, patient and tumor characteristics remained similar whereas use of chemoradiation increased and IMRT was adopted. The introduction of IMRT was associated with improved FFLR, PFS, and OS, and a reduction in acute toxicity as compared to earlier radiation technologies. Level of Evidence: 4 Laryngoscope, 131:E452–E458, 2021